The Influence of User Culture on Website Usability. Issue 154 (October 2021) - Alexander, Rukshan; Thompson, Nik; McGill, Tanya; Murray, David
Highlights: Implementing culturally preferred design elements can positively influence website usability Cultural differences in task completion rates are linked to the use of deep vs broad page navigation structures Heatmaps show that Australian users focus on textual menu items, whereas Chinese users scan the whole page Chinese user performance was less affected by Western page design, suggesting that familiarity plays a role Abstract: Modern web technologies provide a highly customizable and dynamic interaction medium, yet their potential to accommodate individual user preferences and needs is largely untapped. This research empirically demonstrates the significant interaction of user culture with website usability and satisfaction on a set of translated Australian and Chinese websites. By implementing culturally specific design elements it is possible to have a positive influence on user performance and satisfaction, but these relationships are more complex than originally hypothesized. This work highlights the importance of accommodating the different information presentation and interaction styles of culturally diverse users to improve their performance and satisfaction when using the web.